Progress and shortfalls in Europe's defence : an assessment / editors, James Hackett, Ben Schreer. - Hackett, James; Schreer, Benjamin (International Institute for Strategic Studies, 2025)
European NATO members face the dual challenge of Russia's military threat and the United States' expectations about significantly greater 'burden sharing', or even 'burden shifting', for Europe's defence. Their commitment at The Hague Summit in June 2025 to invest 5% of GDP in defence expenditure annually by 2035 acknowledged the need to develop a more sovereign European defence capability and reduce critical dependencies. This IISS Strategic Dossier assesses the progress that has been made in building up NATO European defence capability. It analyses the critical 'hardware gaps' of most European NATO allies relating to intelligence, surveillance and reconnaissance assets, long-range strike systems and integrated air and missile defence. The dossier examines European gaps in the software essential for modern military operations. Although the significant dependence on US providers of hyperscale cloud-computing capacity is unlikely to change soon, efforts by European armed forces to address their 'software gaps' have led to European companies developing significant expertise in edge cloud computing for advanced defence projects. The volume discusses how European countries are looking to speed up procurement, including through legislative changes. Importantly, the trend towards prioritising equipment purchases from domestic or European suppliers continues. The dossier also assesses the prospects for European allies achieving NATO's new investment pledge. This IISS Strategic Dossier was produced in the context of the IISS Prague Defence Summit (PDS) 2025, which has been supported by the government of the Czech Republic.